2022
DOI: 10.1136/neurintsurg-2022-018731
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of wide-necked bifurcation aneurysms with the eCLIPs device: 5-year experience of a single center

Abstract: BackgroundThe endovascular clip system (eCLIPs) is a novel device with both neck bridging and flow-diversion properties that make it suitable for the treatment of wide-necked bifurcation aneurysms.ObjectiveTo describe the clinical and radiologic outcomes of the eCLIPs device, including the first-in-man use of the latest version of the device.MethodsThis is a retrospective case series on all the wide-necked bifurcation aneurysms treated with the eCLIPs device in our center. The immediate and latest radiologic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The eCLIP device is a hybrid device with both neck bridging and flow-diversion properties (98). Recent studies have confirmed its effect in assisting coiling aneurysms, such as in de Vries et al 's study (99) and in Diestro et al 's report (100). The eCLIP device can be used for the treatment of MCA bifurcation aneurysms; however, it has been less frequently reported.…”
Section: Barrel and Eclip Devicesmentioning
confidence: 99%
“…The eCLIP device is a hybrid device with both neck bridging and flow-diversion properties (98). Recent studies have confirmed its effect in assisting coiling aneurysms, such as in de Vries et al 's study (99) and in Diestro et al 's report (100). The eCLIP device can be used for the treatment of MCA bifurcation aneurysms; however, it has been less frequently reported.…”
Section: Barrel and Eclip Devicesmentioning
confidence: 99%